Бушанські мури - Гудченко, З. (Народна творчість та етнографія, 2007)
Busha village of Yampil region in Vinnytsia oblast, is one of the most vivid settlements in the Dniester regions, made great impression on the members of the ethnographic expedition which was formed in October 2007 by Vinnytsia Local Centre of Folklore. Among natural monuments and historico-cultural heritage are geological monument of national importance Haidamatsky Yar, preChristian speos, archeologic fragments of ancient settlements, architectonical fragments of medieval town, terraced village building resulted by rocky landscape. All these monuments make a wonderful multilayer complex, which gives reasons to refer Busha village to very important historical settlements of Ukraine.